Successful and efficient DNA extraction from processed pangolin scales - Xuan, Cai; Ye, Hao-Ting; Tian, En-Wei; Fang, Li; Chan, Li; Yang, Yao-Jun; Liu, Chun-Sheng; Zhi, Chao (Penerbit Universiti Kebangsaan Malaysia, 2019)
A successful method for total DNA extraction from crude and processed pangolin scales was established. After pretreatment in the soaking solution for cleansing, the scales were prepared into fine powders and treated with PBS buffer containing 0.1% collagenase and 0.1% trypsin for 24 h, followed by digestion with proteinase K at 55°C for 120 h. Phenol-chloroform extraction was used to obtain the total DNA. PCR amplification for mitochondrial cytochrome b (cytb) gene was successful using the extracted DNA as the template, and sequencing of the amplified fragments confirmed Manis origin of the scale samples. With an efficiency up to 100%, this method is expected to provide a powerful tool in molecular identification of processed as well as crude pangolin scales.